Spatial dynamics of porcine epidemic diarrhea (PED) spread in the southern Kyushu, Japan - Sasaki, Y.; Toyomaki, H.; Sekiguchi, S.; Sueyoshi, M.; Makita, K.; Otake, S.; Pérez, A.; Álvarez, J. (Elsevier, 2017)
Porcine epidemic diarrhea (PED) was detected for the first time in seven years in Japan in October 2013 in Okinawa Prefecture. By December 2013, PED had spread into Miyazaki and Kagoshima Prefectures in the southern part of Kyushu, one of the regions with the highest farm density in the country. The objective of the study here was to assess the spatial dynamics of PED spread during the 8 months of the epidemic in the southern part of Kyushu between December 2013, the month observed first case in the studied region, and July 2014. Information on location and capacity of all farms in the prefectures (n = 1269) was obtained from a government database containing demographic information for livestock producers. Additionally, data on PED detection (positive or negative) was obtained from the regional Livestock Hygiene Service Center. The Cuzick-Edwards (CE) test, the Knox test, the directional test, and the permutation model of the scan statistic were used to assess the spatio-temporal distribution of the epidemic. PED cumulative farm level incidence was 19.5% (248/1269) through the study period. The highest density of positive farms was observed in the most farm-populated areas of the prefecture. The CE test revealed an extensive degree of spatial clustering, with clustering of positive sites being significant (P < 0.01) up to the 35th level of neighborhood (approximately 5 km in the studied data). The observed-to-expected ratio of cases was maximized at short spatio-temporal distances, with values of the observed-to-expected ratio of cases maximized when the thresholds were set at 2 km and 10 days, respectively. A significant (P < 0.01) direction of spread was detected towards the northeastern direction. The permutation model detected five significant (P < 0.01) clusters occurring at different stages of the epidemic wave. The strong spatio-temporal clustering of PED-infected farms during the first 6 months of the epidemic in the southern part of Kyushu is consistent with results obtained elsewhere and demonstrates the rapid spread of the virus in naïve populations.